SMART convex mirror (By Bio-Pro Sales and Service Sdn Bhd) / Nur Liyana Abdul Hadi - Abdul Hadi, Nur Liyana (2020)
Bio-pro desire to introduce to the consumers a new product which is the ‘SMART convex mirror’ with built-in warning light and wireless magnetic sensor technology. With the existing of warning light and wireless sensor technology, this convex mirror can be used for drivers who having vision issues especially during nighttime at blind curve area. The company offers business to business which that exchange of products, services, or information between two businesses, rather than between a company and individual consumers. Potentially the major purchasers for the SMART convex mirror are from the local governments in Malaysia that involve in road and traffic development in certain area. For instances, city council covers development in city or urban area while district council covers most in suburban area. Local governments are also usually referred as local authority is an organization that is officially responsible for all the public services and facilities in a particular area. The product is installed at the blind curve area or in targeted area, so it is appropriate to have people who are knowledgeable about the road development aspects.